The influence of intrinsic and extrinsic employee rewards on turnover intention among Malaysian hospitality employees - Sanggari Krishnan; Balan Rathakrishnan (Asian Scholars Network, 2024)
This quantitative correlational research aims to study the influence of intrinsic and extrinsic employee rewards on turnover intention among Malaysian hospitality employees. It also aims to identify the strongest predictor influencing turnover intention in the current context. The problem investigated was the increasing level of turnover, which relates to the lack of rewards in this industry. Past research has mixed and inconsistent findings related to these variables. Moreover, limited research focuses on the connection between these variables in the Malaysian hotel sector. Conversely, current research focuses on the importance of both intrinsic and extrinsic rewards in determining turnover intention. This cross-sectional survey design consisted of a purposive sample of 402 Malaysian hotel workers. Data were collected using two instruments, namely the Employee Rewards Questionnaire and the Anticipated Turnover Scale (ATS). Pearson correlation analysis showed that there was a significant inverse relationship between both types of employee rewards and turnover intention. The Multiple Regression analysis yielded significant results that showed the relationship between employee rewards and turnover intention as suggested by previous research. It was concluded that extrinsic rewards influence turnover intention better than intrinsic rewards in this context. Understanding these relationships contributed to a new dimension of dealing with the turnover crisis in the hospitality industry. Organisations should focus on enhancing extrinsic rewards because they are crucial in satisfying employees and retaining them.